Model assessment of corporate environmental responsibility applied to production chain agrobusiness: analysis, considerations and critical - Alcântara, Valderí de Castro; Macedo, Alex dos Santos; Silva, Edson Arlindo; Ferreira, Ana Cristina; Mendes, Alcindo Cipriano Argolo (Revista de Administração da UFSM, 2017)
This article presents the development, factor structure and discussion of a model for assessing the appropriate corporate environmental responsibility to agribusiness production chain. The empirical research was conducted with companies in the Alto Paranaíba, Minas Gerais and the data collected through questionnaire was used and scale. With the factor analysis extracted five factors: Commitment and environmental activity (COMAMB = 3.20), Environmental impacts (GIMA = 4.13), Education and environmental awareness (ECAM = 3.52), Involvement with stakeholders (ENVOLV = 3.69) and Resource economics (ECON = 4.23). The overall index of corporate environmental responsibility was 0.6885. It was observed that the companies analyzed, on average, do not care about education and environmental awareness and have a low level of commitment to actions for the preservation and protection of the environment. However, they seek to maintain an efficient management of environmental impacts and which involve such issues with their stakeholders. And so, perform 'green economy' and 'green marketing' of their activities. Finally, the debate that corporate environmental responsibility is a strategy where the companies operate, guided by a strategic and economic rationality.